Defensive impact of foliar applied potassium nitrate on growth linked with improved physiological and antioxidative activities in sunflower (Helianthus annuus l.) hybrids grown under salinity stress - Aslam, Anisa; Khan, Shahbaz; Ibrar, Danish; Irshad, Sohail; Bakhshi, Ali; Gardezi, Syed Tahir Raza; Ali, Madad; Hasnain, Zuhair; Al-Hashimi, Abdulrahman; Noor, Mehmood Ali; Brestic, Marian; Skalicky, Milan; et al. (Multidisciplinary Digital Publishing Institute, 2021)
Salt stress is recognized to negatively influence the fundamental processes in plants regarding growth and yield. The sunflower (Helianthus annuus L.) is considered an important industrial crop because of the good quality of oil it produces that can be used for cooking purposes. The exogenous application of potassium (K) has been reported to enhance abiotic resistance and increase yield in crops. Here, we explored the impact of foliar-applied K at 500 ppm on the physiological and biochemical traits, antioxidant activities, and growth attributes of sunflower grown under salt stress (140 mM NaCl). The findings indicated that salinity stress adversely affected photosynthesis and various gas exchange characteristics. Foliar applied K markedly improved the stomatal conductance, transpiration rate, water use efficiency, CO2 assimilation rate, total soluble proteins, chlorophyll pigments, and upregulated antioxidant system, which are responsible for the healthy growth of sunflower hybrids grown under salinity stress. The shoot and root lengths, plant fresh and dry weights, and achene weight were significantly increased by K application. Overall, foliar applied K significantly improved all of the aforementioned attributes and can attenuate the deleterious influences of salinity stress in sunflower.